2020
DOI: 10.1021/acs.jafc.0c04370
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Supplementation Attenuates DSS-Induced Colitis via Mediating Gut Barrier Integrity, Inflammatory Responses, and Reshaping Gut Microbiome

Abstract: Sesamol, a liposoluble lignan extract, has already been proved to possess potent anti-inflammatory properties, and it could also regulate gut dysfunction. The purpose of the present research is to explore the protective effect of sesamol on colitis mice. In the current research, sesamol treatment (100 mg/kg bodyweight/day) for 6 weeks inhibited the dextran sulphate sodium (DSS)induced bodyweight loss of mice. Transmission electron microscopy and hematoxylin and eosin staining results showed that the DSS-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 45 publications
(80 reference statements)
7
74
0
Order By: Relevance
“…Moreover, WB results also showed that treatment with cinnamaldehyde significantly up-regulated the protein expression levels of TJs such as ZO-1, claudin-1, and occluding (Figure 2F). Consistent with these results, a few other phytochemicals, such as flavonoids and polyphenols, have also been indicated to enhance TJ functions and gut integrities (22)(23)(24).…”
Section: Cinnamaldehyde Supplementation Improved the Gut Barrier Integrity In Newly Weaned Ratssupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, WB results also showed that treatment with cinnamaldehyde significantly up-regulated the protein expression levels of TJs such as ZO-1, claudin-1, and occluding (Figure 2F). Consistent with these results, a few other phytochemicals, such as flavonoids and polyphenols, have also been indicated to enhance TJ functions and gut integrities (22)(23)(24).…”
Section: Cinnamaldehyde Supplementation Improved the Gut Barrier Integrity In Newly Weaned Ratssupporting
confidence: 65%
“…Tight junctions (TJs) also play important roles in the maintenance of intestinal permeability, which is considered to determine selective para-cellular absorption ( 18 ). Previous studies have shown that the zonula occludins (ZO), claudin family proteins, and occludin are essential components of TJs in the epithelial barrier ( 22 ). The major functions of TJs are to maintain the integrity of the intestinal epithelial barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation analysis was performed based on the experimental data to identify a correlation among bacteria, inflammatory cytokines, TJ proteins, and rate of apoptosis in DSS-treated mice [ 8 ]. The data indicated a notable correlation between the proportion of bacteria and other parameters ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, novel drugs that treat or target other aspects of the disease are needed. Among these multiple factors involved in UC, gut barrier damage has been identified as a vital etiological factor in colitis [ 7 , 8 ]. The intestinal barrier—the first mechanical defense against pathogens and antigens—is formed by tight junctions (TJs), adhesive junctions, and desmosomes between epithelial cells (ECs) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation